Relationships among physical activity, sleep, and cancer-related fatigue: results from the international ColoCare Study - Crowder, Sylvia L.; Li, Xiaoyin; Himbert, Caroline; Viskochil, Richard; Hoogland, Aasha I; Gudenkauf, Lisa M; Oswald, Laura B; Gonzalez, Brian D; Small, Brent J; Ulrich, Cornelia; Ose, Jennifer; Peoples, Anita R; et al. (Annals of behavioral medicine, 2024)
Risk factors for cancer-related fatigue are understudied in colorectal cancer.This study aimed to address this critical gap in the literature by (a) describing changes in colorectal cancer-related fatigue and health behavior (physical activity, sleep problems) and (b) examining if physical activity and sleep problems predict fatigue trajectories from baseline (approximately at the time of diagnosis), to 6- and 12 months after enrollment.Patients participating in the international ColoCare Study completed self-report measures at baseline (approximately time of diagnosis), 6-, and 12 months assessing physical activity using the International Physical Activity Questionnaire (IPAQ) and fatigue and sleep using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-QLQ-C30). Mixed-effect models examined changes in physical activity, sleep problems, and fatigue. Cross-lagged panel models examined bidirectional relationships between physical activity or sleep and fatigue across time.Colorectal cancer patients (n = 649) had a mean age of 61 ± 13 years. Most were male (59%), non-Hispanic White (91%), diagnosed with Stages III-IV (56%) colon cancer (58%), and treated with surgery (98%). Within-person cross-lagged models indicated higher physical activity at Month 6 was associated with higher fatigue at Month 12 (β = 0.26, p = .016). When stratified by cancer stage (I-II vs. III-IV), the relationship between physical activity at Month 6 and fatigue at Month 12 existed only for patients with advanced cancer (Stages III and IV, β = 0.43, p = .035). Cross-lagged associations for sleep and fatigue from baseline to Month 6 were only observed in patients with Stages III or IV cancer, however, there was a clear cross-sectional association between sleep problems and fatigue at baseline and Month 6.Within-person and cross-lagged association models suggest fatiguability may become increasingly problematic for patients with advanced colorectal cancer the first year after diagnosis. In addition, sleep problems were consistently associated with higher fatigue in the first year, regardless of cancer stage.The international ColoCare Study was registered on clinicaltrials.gov, NCT02328677, in December 2014.Within-person and cross-lagged association models suggest fatiguability may become increasingly problematic for patients with advanced (Stages III and IV) colorectal cancer the first year after diagnosis.